EVALUATION OF THE IMPLEMENTATION OF THE STUNTING REDUCTION ACCELERATION PROGRAM POLICY WITH THE FAMILY DEVELOPMENT POPULATION PROGRAM AT THE BKKBN REPRESENTATIVE OFFICE OF WEST SUMATRA PROVINCE - Santi Hariani; Hassan, Datin Hafizah Che; Das, Sreemoy Kanti (Indonesian Journal of Social Science and Education (IJOSSE), 2025)
Stunting is a growth and development disorder in toddlers that impacts their physical, cognitive, and productivity development. Stunting can be prevented by optimizing family roles and functions. Family resilience isthe ability of a family to adapt, overcome problems, and face pressure from within and outside so that it can continue to function harmoniously and achieve the well-being of its membersThe purpose of this study was to determine the implementation of the stunting reduction acceleration program policy with the Population and Family Development Program at the BKKBN Representative Office of West Sumatra Province in accordance with Presidential Regulation Number 72 of 2021 concerning the acceleration of stunting reduction. The research method used a qualitative approach with policy studies. The research informants numbered 28 people with data collection techniques through observation, in-depth interviews, focus group discussions and document reviews. The results of the research on the input component, namely Policy, human resources, facilities and infrastructure and funds for the stunting reduction acceleration program did not comply with the provisions. The process component, namely the suboptimal assistance and intervention by the Stunting Officer Unit, Technical Assistant and the family assistance team in utilizing data on families at risk of stunting and the lack of commitment and synergy between the Central, regional and village governments in implementing the acceleration of stunting reduction convention. The output component, namely the national sensitive intervention program indicators have not met the national target, the outcome component, namely Some of the main indicators of the family development population program have not reached the specified target and stunting cases have increased and are above the national target, the need to strengthen the synergy and commitment of the regional government and increase the knowledge and commitment of the family assistance team in implementing the stunting program. The conclusion is that the implementation of the accelerated stunting reduction program is in accordance with regulations, but is not yet optimal in terms of policy, human resources, facilities and infrastructure, and financing. Coordination and collaboration between the government and the community, optimization of data on families at risk of stunting, and regular monitoring and evaluation are needed.